Role of cultural values and protean orientation on career success criteria. - Guo, Shuqi. (2008)
This study examines the role of cultural values, using Hofstede’s 5 cultural dimensions, and protean orientation on career success criteria. This study also examines the predictive role of protean orientation as an independent variable and as a mediator in the relationship between cultural values and career success criteria.